1998
DOI: 10.1007/s004020050258
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year follow-up of a bicondylar unlinked knee endoprosthesis with particular reference to mid-term results

Abstract: This analysis, submitted retrospectively, evaluates 603 PCA-type or Duracon-type knee endoprostheses implanted in 527 patients over a 10-year period. In addition, the X-rays available in a group of 138 patients (100 women and 38 men) from the entire patient population were analysed. All of these 138 patients were invited to come in for a follow-up examination. The invitation was accepted by 80 patients. As well as radiological and physical examination, these patients were asked about their subjective physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
2
6
0
1
Order By: Relevance
“…The authors determined that the Duracon prosthesis had a survivorship rate of 90% after a 6-year follow-up (95% CI, 81%-99%). Similarly, other studies have reported high survival rates of 97%-99% and 96%-98.6% for a short-term and mid-term follow-up in Duracon TKA patients [7,8,[10][11][12].…”
Section: Discussionmentioning
confidence: 97%
“…The authors determined that the Duracon prosthesis had a survivorship rate of 90% after a 6-year follow-up (95% CI, 81%-99%). Similarly, other studies have reported high survival rates of 97%-99% and 96%-98.6% for a short-term and mid-term follow-up in Duracon TKA patients [7,8,[10][11][12].…”
Section: Discussionmentioning
confidence: 97%
“…Other authors have confirmed the superiority of a cementless implantation technique. Apart from better functional results, less polyethylene abrasion due to delamination is seen and the durability of the TKA is improved with a lower rate of aseptic loosening [10,11,49]. Furthermore, a cementless implantation technique provides better conditions for anchorage of the endoprosthesis, if revision surgery becomes necessary [17,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, TKA is only indicated in 12% of cases of posttraumatic osteoarthrosis (POA) in Germany [6]. In published retrospective studies, this percentage is between 0% and 6% [2,[7][8][9][10][11][12][13][14][15][16][17]. Changes in leisure activities undertaken by younger patients and the increasing popularity of sports that carry a high risk of injury have led to an increase in the incidence of POA [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies on early (two to five years [12, 21, 29]) and mid-term (five to ten years [10, 13, 15]) survival results for the Duracon TKA have been published with survival rates between 97 and 99 % and 96–98.6 %, respectively. Long-term survival data is available mainly from the Scandinavian Knee Arthroplasty Registers [11, 24, 26].…”
Section: Introductionmentioning
confidence: 99%